2006
DOI: 10.1246/cl.2007.108
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Self-aggregates of Phthalocyanine Based on Zn–O Coordination

Abstract: α-Aryl/alkoxy-substituted phthalocyanines (Pcs) were synthesized and the formation of J-type self-aggregation for zinc phthalocyanines has been observed in organic non-coordinating solvents. The mechanism of the formation of this self-assembly was studied by UV–vis spectroscopy, fluorescence spectroscopy and MALDI-TOF MS, which revealed that it was stabilized by Zn–O self-coordination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…Huang et al. have reported that inclusion of equatorial ether groups in ZnPc constructs led to well‐defined absorption with an approximately 30–40 nm redshifted absorbance and corresponding redshifted fluorescence,32 which was also observed for similar constructs by Cong et al 33. Recently, Morisue et al.…”
Section: Resultsmentioning
confidence: 65%
“…Huang et al. have reported that inclusion of equatorial ether groups in ZnPc constructs led to well‐defined absorption with an approximately 30–40 nm redshifted absorbance and corresponding redshifted fluorescence,32 which was also observed for similar constructs by Cong et al 33. Recently, Morisue et al.…”
Section: Resultsmentioning
confidence: 65%
“…Rare cases red-shifted bands have been observed corresponding to J-type aggregation of the phthalocyanine molecules. Generally, J-aggregates of Pc occurred by utilizing the coordination of the side substituent from one Pc molecule to the central metal ion in a neighbor [7][8][9][10][11]. The substituted zinc Pcs in non-coordinated organic solvents, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time the lowering of the molecular symmetry along with the coordinating nature of the peripheral environment has allowed demonstrating the fact of the phthalocyanine complexes dimerization [11]. It was shown that the self-assembled phthalocyanine J-type dimers and aggregates can exist only in solutions [11][12][13][14] and therefore, the detailed studies of their physicochemical and photophysical properties are strongly hindered. We were the first to synthesize of the thermal and chemical stable dimers of J-type, in which phthalocyanine macrocycles with antiparallel arrangement exhibit strong intermolecular p-p interactions due to their close contact and the possibility of formation of coordination bonds between the central metal ions and oxygen atoms of the peripheral OH-groups [15,16].…”
Section: Introductionmentioning
confidence: 99%